Tributação ótima sobre o consumo: uma aplicação com o ICMS para o estado de Alagoas para o período 2008-2009 - Freitas, Tatiane Tenório da Gama Leite de (2019)
The optimal taxation on consumption explores two of the four criteria considered for the analysis of a tax, are the criteria of efficiency and equity. The ICMS, in turn, is a state tax that focuses on the consumption of goods and services and is considered the main tax collection instrument of the states. In this situation, in spite of the efficiency in the collection of the same, compared to other taxes, ICMS tends to be regressive and therefore not equitable. In view of this, the present research has as objective to apply the theory of the optimal taxation for the ICMS of the state of Alagoas, considering different weights of aversion to the inequality of the government. For this purpose, the maximization of a social welfare function restricted to government revenue is carried out, taking into account the criteria of efficiency and equity. The maximization will be done using the Genetic Algorithm computational method and will use the household consumption data, made available by POF / IBGE, and the revenue collected from the ICMS, made available by CONFAZ, both referring to the years of 2008 and 2009. The main results show that the greater the concern with government equity, the lower the rates of the goods of need, which are the most consumed, in proportion to income, by low-income families, tend to be lower, so they are goods such as food, medicines and school supplies. The opposite happens with goods that have a higher fraction of consumption by high-income households, such as vehicle purchase and telephone, TV and internet package.